Exploring Methods for Assessing Critical Thinking: Insights from Qualitative Study - Mastul, Al-Rashiff Hamjilani; Sulisworo, Dwi (Jurnal Studi Multidisiplin Qomaruna, 2024)
This article explores the various methodologies and approaches used in assessing critical thinking skills. The study was carried out by utilizing secondary data obtained from easily accessible literature sources on the internet which were discussed qualitatively regarding four main issues in assessment: Observation, Evidence Evaluation, Problem-Solving Tasks, and Decision-Making Exercises. Through descriptive analysis, the importance of integrating relevant measurement techniques into questions that focus on critical thinking skills is explained. The findings of this study underscore the important role of a comprehensive evaluation approach in equipping individuals with the essential critical thinking skills necessary to navigate the complexity of modern challenges and make informed decisions in diverse contexts.